Heidegger - the formation of modern aesthetics and art as the appearance of culture - Radovanović, Saša Ž. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
The paper analyzes Heidegger’s views on aesthetics and art in the epoch of the new century. First, it is shown how Heidegger defines the general concept of aesthetics. Then the role of Descartes’ philosophy in establishing the Being and the truth as a certainty in the epoch of the new century is shown. Modern aesthetics and art are formed within such a change of being and truth. Modern aesthetics and art are formed within such a change of being and truth. In modern aesthetics, feeling and beauty are connected and taste, subjective judgment, is placed as a central concept. On the other hand, art is presented as a cultural phenomenon that distances itself from the Christian concept of art.